2021
DOI: 10.3390/foods10123086
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curcumin Alleviated Aflatoxin B1-Induced Acute Liver Damage in Ducks by Regulating NLRP3–Caspase-1 Signaling Pathways

Abstract: Aflatoxin B1 (AFB1) is a mycotoxin widely distributed in animal feed and human food; it represents a serious threat to human and animal health. This study investigates the mechanism by which dietary curcumin protected liver against acute damage caused by AFB1 administration in ducks. One-day-old male ducks (n = 450) were randomly assigned to three groups, the control group, the AFB1 group, and the AFB1 + curcumin group; the first group were fed with basic diet, while the third group was fed basic diet containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…As the conventional methods of aflatoxin detection have some limitations like being expensive and time consuming, there is a need for some emerging novel methods that are simpler, easier, cheaper more reliable and selective. In this regard, the biosensors for aflatoxins detection are of interest in food safety and control (Jin et al, 2021;Xue et al, 2019;El Sheikha et al, 2018) Biosensors A biosensor is applying a selective detection by the help of a biological recognitive element to discover the chemical combinations with electrical, optical and thermal signals (Li et al, 2021). Biosensors have a bio-recognition element, a transducer and a detector.…”
Section: Spectroscopic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the conventional methods of aflatoxin detection have some limitations like being expensive and time consuming, there is a need for some emerging novel methods that are simpler, easier, cheaper more reliable and selective. In this regard, the biosensors for aflatoxins detection are of interest in food safety and control (Jin et al, 2021;Xue et al, 2019;El Sheikha et al, 2018) Biosensors A biosensor is applying a selective detection by the help of a biological recognitive element to discover the chemical combinations with electrical, optical and thermal signals (Li et al, 2021). Biosensors have a bio-recognition element, a transducer and a detector.…”
Section: Spectroscopic Methodsmentioning
confidence: 99%
“…As the conventional methods of aflatoxin detection have some limitations like being expensive and time consuming, there is a need for some emerging novel methods that are simpler, easier, cheaper more reliable and selective. In this regard, the biosensors for aflatoxins detection are of interest in food safety and control (Jin et al , 2021; Xue et al , 2019; El Sheikha et al , 2018)…”
Section: Spectroscopic Methodsmentioning
confidence: 99%
“…Additionally, several clinical studies have shown that curcumin has a strong therapeutic potential for treating a few chronic illnesses, including pulmonary, cancer, neurological, cardiovascular, infectious, neoplastic, psychiatric, and metabolic disorders [ 68 ]. Not surprisingly, several in vitro and animal experimental studies confirmed that curcumin supplementation could offer strong protective effects against AFB1-induced liver injury, mutagenicity, hepatocarcinogenicity, renal dysfunction, ileum damage, immune toxicity via regulating multiple above-mentioned targets [ 26 , 34 , 60 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The detailed molecular pathways are discussed in the section below.…”
Section: Biological Properties Of Curcuminmentioning
confidence: 99%
“…Wang et al discovered that oral administration of AFB1 at 750 μg/kg BW for 30 days might produce significant kidney oxidative damage, as demonstrated by the loss of antioxidative enzyme (e.g., CAT and SOD) activities and the decreases in GSH levels and increases in hydrogen peroxide (H 2 O 2 ) and levels of MDA in the kidney tissues; meanwhile, oral administration of curcumin supplementation could significantly inhibit AFB1-induced oxidative stress by upregulating the GSH content and SOD and CAT activities [ 70 ]. Consistently, curcumin supplementation could also significantly improve AFB1-exposure-induced cytotoxicity in bovine fetal hepatocyte-derived cells, renal damage in mice and chickens, and liver, spleen, and ileum damage in ducks by inhibiting the production of ROS and oxidative stress through the upregulation of activities of antioxidant enzymes and levels of antioxidants or free radical scavenging [ 60 , 69 , 70 , 72 , 74 , 75 ]. Very recently, Damiano et al found that curcumin supplementation significantly inhibits the expression of NADPH Oxidase 4 (NOX4) mRNA and protein, thus inhibiting AFB1-induced renal oxidative stress in chicken [ 75 ].…”
Section: Curcumin’s Protective Role In Preventing Afb1-induced Toxici...mentioning
confidence: 99%
“…Two of the most prevalent and well-known mycotoxins are ochratoxin A (OTA) and aflatoxin B1 (AFB1) [5][6][7][8][9][10]. These toxins can contaminate food and feed products, which in turn can lead to a range of adverse effects on animal health and nutrition [11][12][13]. In pigs, the exposure to OTA and AFB1 has been shown to impair feed intake, growth performance, and immunity, as well as increase oxidative stress and the risk of various diseases [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%